Comparison Between Laparoscopic and Robotic Surgery in Elderly Patients With Endometrial Cancer: A Retrospective Multicentric Study - Corrado, Giacomo; Vizza, Enrico; Perrone, Anna Myriam; Mereu, Liliana; Cela, Vito; Legge, Francesco; Hilaris, Georgios; Pasciuto, Tina; D’Indinosante, Marco; La Fera, Eleonora; Certelli, Camilla; Bruno, Valentina; et al. (Frontiers in Oncology, 2021)
Introduction Elderly endometrial cancer (EEC) patients represent a challenging clinical situation because of the increasing number of clinical morbidities. In this setting of patients, minimally invasive surgery (MIS) has been shown to improve surgical and clinical outcomes. The aim of this study was to evaluate the peri-operative and oncological outcomes of EEC patients who had undergone laparoscopic (LS) or robotic surgery (RS). Materials and Methods This is a retrospective multi-institutional study in which endometrial cancer patients of 70 years or older who had undergone MIS for EC from April 2002 to October 2018 were considered. Owing to the non-randomized nature of the study design and the possible allocation biases arising from the retrospective comparison between LS and RS groups, we also performed a propensity score-matched analysis (PSMA). Results A total of 537 patients with EC were included in the study: 346 who underwent LS and 191 who underwent RS. No significant statistical differences were found between the two groups in terms of surgical and survival outcomes. 188 were analyzed after PSMA (94 patients in the LS group were matched with 94 patients in the RS group). The median estimated blood loss was higher in the LS group (p=0.001) and the median operative time was higher in the RS group (p=0.0003). No differences emerged between LS and RS in terms of disease free survival (DFS) (p=0.890) and overall survival (OS) (p=0.683). Conclusions Our study showed that when compared LS and RS, RS showed lower blood losses and higher operative times. However, none of the two approaches demonstrated to be superior in terms of survival outcomes. For this reason, each patient should be evaluated individually to determine the best surgical approach.